Analisis Aspek Kepribadian Tokoh Utama dalam Novel Cadl karya Triskaidekaman (Tinjauan Psikologi Sastra) - Dina Husnul Maria; Slamet Triyadi; Imam Muhtarom (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the personality of the character Lamin as the main character in the novel Cadl by Triskaidekaman by using a literary psychology approach. The theory used is humanistic psychology from Abraham Malow which discusses the five levels of human needs. The research approach used is descriptive qualitative approach and the method used in this research is descriptive analysis method. The data source used in this research is the novel Cadl by Triskaidekaman. The results and discussion of this research start from the intrinsic elements which include the theme, plot or plot, characters and characterizations, and finally the setting. The aspects of humanistic psychology contained in Triskaidekaman's CADL novel include basic physiological needs, the need for security, the need for love and belonging, the need for self-esteem and the need for self-actualization